2016
DOI: 10.1136/annrheumdis-2016-eular.1677
|View full text |Cite
|
Sign up to set email alerts
|

THU0563 Characterization of A Group of 6 Patients with Mevalonate Kinase Deficiency: Symptoms and Treatment with IL-1 Inhibitors

Abstract: BackgroundMevalonate kinase deficiency (MKD) is a rare autosomal recessive autoinflammatory disease caused by mutations in MVK gene. MKD patients typically have an early onset of symptoms including recurrent episodes of high fever, abdominal pain, diarrhea and vomiting, arthralgia and lymphadenopathy. However not all patients have typical clinical picture of MKD.MethodsWe conducted a retrospective analysis of clinical features of six patients (4 females, 2 males) with MKD (confirmed by identification of MVK ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…70 At long-term follow-up, anakinra showed a 100% CR (online supplementary figure 3A–B). 82 Other observational studies revealed that anakinra decreased the AIDAI score, 83 and attained complete clinical response in 52% and functional status improvement in 81% of patients. 85…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…70 At long-term follow-up, anakinra showed a 100% CR (online supplementary figure 3A–B). 82 Other observational studies revealed that anakinra decreased the AIDAI score, 83 and attained complete clinical response in 52% and functional status improvement in 81% of patients. 85…”
Section: Resultsmentioning
confidence: 98%
“…59 Patients who achieved a CR with anakinra ranged from 40% 34 to 100% 82 at long-term follow-up (online supplementary figure 2A–B). Other observational studies showed that anakinra was effective in improving AIDAI score 36 83 or DAS, 57 58 in attaining disease control, 73 clinical/biochemical remission, 84 85 complete/partial resolution of CAPS symptoms, 38 43 45 49 51 60 62 64 79 PROs, 36 58 79 85 CHQ-PF50 60 and DLQI. 64 Seven studies also demonstrated improvement or stabilisation with anakinra in neurological outcomes (eg, migrainous headache, papilledema), 45 60 62 hearing loss, 30 5557 60 62 and visual acuity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations